Análise dos preços do boi e da carne nos diferentes elos da cadeia produtiva - Teixeira, Camilla Trevisan (2018)
The production cycles of the beef chain are influenced by several factors that affect the prices paid by the slaughterhouse to the producer and the prices of the meat in the retail. The objective of this study was to evaluate the prices of cattle and beef in the different links of the production chain during twelve consecutive months in the central region of Rio Grande do Sul. The prices paid by cattle and beef were collected every fortnight in four links of the production chain: lean cattle producer, fat cattle producer, slaughterhouses and retailers. Statistical analysis included analysis of variance (ANOVA), Tukey's test (P<0.05) and Pearson's linear correlation by SAS® Studio (2016). The first quarter of the year presented the highest prices for all links in the production chain while the third quarter presented the lowest price. Retail sources had similar annual average prices between them. The highest correlation values occurred between the lean cattle price (0.810), the fat cattle price (0.855) with the selling price of the meat by the slaughterhouse. Lower correlations occurred between the price of meat sold by the retailer with the selling price of the meat by the slaughterhouse (0.425). The fat cattle price was the largest coordinator of the other prices in the beef chain (0.886), and is the biggest regulator of the lean cattle price, the price of meat sold to retail, but not the price of meat sold to the consumer.